2019
DOI: 10.1007/s00468-019-01841-6
|View full text |Cite
|
Sign up to set email alerts
|

Fire facilitates warming-induced upward shifts of alpine treelines by altering interspecific interactions

Abstract: Key messageModerate-severity fire disturbances can accelerate upslope shifts of alpine treelines by reducing interspecific interactions, providing additional evidence for the species interaction mechanism in controlling treeline dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 66 publications
(110 reference statements)
1
15
0
2
Order By: Relevance
“…How species respond to changing climates at local scales will depend on how edaphic and biological characteristics interact with species physiological limits, traits such as dispersal, and interactions with disturbance (type, frequency, severity). While climate is considered a key determinant of alpine treeline position [1], and hence treeline position is likely responsive to climate warming, disturbance may also play a critical but poorly understood role [12,13,49]. Using a revisitation approach at the alpine treeline in Australia where fire has been both extensive and recurrent during the last few decades [44], we found that a limited number of saplings of the alpine treeline species E. pauciflora recruited above the treeline, but this depended on the frequency of fire.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…How species respond to changing climates at local scales will depend on how edaphic and biological characteristics interact with species physiological limits, traits such as dispersal, and interactions with disturbance (type, frequency, severity). While climate is considered a key determinant of alpine treeline position [1], and hence treeline position is likely responsive to climate warming, disturbance may also play a critical but poorly understood role [12,13,49]. Using a revisitation approach at the alpine treeline in Australia where fire has been both extensive and recurrent during the last few decades [44], we found that a limited number of saplings of the alpine treeline species E. pauciflora recruited above the treeline, but this depended on the frequency of fire.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how disturbance, such as fire, impacts on treeline persistence and expansion is clearly crucial for interpreting treeline population dynamics [49,59]. Fires, particularly at short-intervals, have been found to cause treeline depression across a range of global treelines [28,[60][61][62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By opening gaps, wildfires may help species replacement to occur more quickly than in closed conditions, especially in ecosystems dominated by non‐resprouting (fire‐killed) species (eg Wang et al . ). In addition, these new gaps for recruitment select for individuals (ie genotypes) better suited to the new climate, thereby enhancing adaptation to drier conditions.…”
Section: Regulating Servicesmentioning
confidence: 97%
“…在 青海玉树、西藏昌都和林芝地区, 川西云杉树线爬升 25 m [27] , 而急尖长苞冷杉树线仅上升0~9 m [28] . 在滇西 北的横断山区, 长苞冷杉和大果红杉树线爬升幅度分 别为19~28和0~67 m [25,29,30] . 总之, 过去100年来青藏高 [25] .…”
Section: 温度是影响植被生长期变化的最主要驱动因子之 一 研究表明温度每升高1°c 青藏高原草地返青期平unclassified